Enhancing brand equity through emotions and experience: the banking sector - Loureiro, S. M. C.; Sarmento, E. M. (International Journal of Bank Marketing, 2018)
Purpose The banking sector is devoted to attracting Generation Y customers with their particular tastes and interests. The purpose of this paper is to explore for the first time how bank experience influences emotions and perception of brand equity. Using the stimulus–organism–response (S–O–R) framework, the authors consider the perception of brand equity as the outcome. Design/methodology/approach A panel based on the method of Walsh and Beatty (2007) with completed and usable questionnaires was used to test the proposed model. The authors selected a sample of 211 respondents. After eliminating some inconsistencies, a final data sample consisted of 205 usable survey participants (male: 58 percent; female: 42 percent). Findings Executional excellence, staff engagement and value for money are the most relevant indicators in shaping the overall bank experience. Pleasure is the positive emotion that most enhances the perception of brand equity. Originality/value This study extends the S–O–R model by employing dimensions of experience as stimuli and brand equity as response. The study demonstrates the role of emotions (particularly pleasure) in enhancing brand equity among individuals from the Generation Y.